124k views
1 vote
For each pair of function f and g below, find f(g(x)) and g(f(x)).

a. f(x)=3/x,x=/= 0
b. g(x)=3/x, x=/=0
c. f(x)=x+4
d. g(x)=-x+4

User Petru
by
5.4k points

1 Answer

5 votes

Answer:

(a) and (b)


f(g(x)) = g(f(x)) = x

(c) and (d)


f(g(x)) =-x + 8


g(f(x)) = x + 8

Explanation:

Given

(a) to (d)

Required

Find f(g(x)) and g(f(x)) for each pair

For (a) and (b), we have:


f(x) = (3)/(x)


g(x) = (3)/(x)

Calculate f(g(x))


f(x) = (3)/(x)


f(g(x)) = (3)/(g(x))

Substitute 3/x for g(x)


f(g(x)) = (3)/(3/x)

Rewrite as:


f(g(x)) = 3/(3)/(x)


f(g(x)) = 3*(x)/(3)


f(g(x)) = x

Since f(x) = g(x), then:


f(g(x)) = g(f(x)) = x

For (c) and (d)


f(x) =x + 4


g(x) =-x + 4

Solving f(g(x)), we have:


f(x) =x + 4


f(g(x)) =g(x) + 4

Substitute
g(x) =-x + 4


f(g(x)) =-x + 4 + 4


f(g(x)) =-x + 8

Calculating g(f(x))


g(x) =-x + 4


g(f(x)) = -f(x) + 4

Substitute:
f(x) =x + 4


g(f(x)) = x + 4 + 4


g(f(x)) = x + 8

User Rajeev Mehta
by
5.0k points